Branding and its Competitive Advantage in the Consumer Electronics Industry - Singhania, Pritha (2006)
Branding though not a new concept to management has come into spotlight lately and being an impending business strategy is exercised by all leading and upcoming companies who want to leave an impression in the minds of their customers as to who they are. Consumer electronic products belong to that category of products where they are bought and sold on the basis of the name tag they hold and thus being a good brand is one or their main USPs. Therefore, through the help of my dissertation I want to explain the competitive advantage a good brand provides to a consumer electronics product over its rivals. Supported by a rigorous literature review in the theories and concepts of consumer electronics marketing and branding, followed by a discussion and recommendation on the basis of questionnaires, this research has attempted to uncover the components of powerful consumer electronic brands. Consumer electronic brands have been shown to comprise of a complex structure of advanced technology, innovation in product improvement, dedication to product quality, a well-built set of values and planned brand management. Lastly, suggestions are provided to consumer electronic brand managers with an intention to offer solutions to construct a strong and everlasting brand.